Cooperative behavior in adolescents: a contribution of empathy and emotional regulation? - Martínez-Velázquez, Eduardo Salvador; Ponce-Juárez, Sandra Pamela; Díaz Furlong, Alfonso; Sequeira, Henrique (Frontiers in Psychology, 2024)
Aim This study aims to identify different levels of empathy and emotional regulation along adolescent years and their relationship with cooperative behavior. Methods Eighty healthy males were divided into four age groups: 20 Early Adolescents, 20 Middle Adolescents, 20 Late Adolescents and 20 Adults. Participants responded to empathic and emotional regulation scales, then were assigned to an unknown partner to perform the prisoner’s dilemma paradigm. Results The statistical analyses allowed to distinguish the groups on the basis of the components making up the two scales: scores on the Perspective Taking component were higher for Adults and Late Adolescents participants than for Middle Adolescents and Early Adolescents groups (p < 0.05); scores on the Personal Distress component were higher for Early Adolescents group than for Late Adolescents and Middle Adolescents groups (p < 0.05); scores on the Difficulties engaging in goal directed behavior component were higher for Middle Adolescents and Early Adolescents groups than for Adults group (p < 0.05). We observed differences between groups (p < 0.001) with higher number of cooperation responses in Adults compared to Middle Adolescents (p < 0.05) and Early Adolescents groups (p < 0.001). Discussion These findings suggest that the cooperative behavior changes during the different stages of adolescence seem to be related to the development of empathy and emotional regulation components.